Recent trends in the application of cold plasma for the modification of plant proteins - A review - Somnath Basak; Uday S. Annapure (Future Foods, 2022)
Plant proteins are gaining attention in recent times. Apart from the greater sustainability and environment-friendliness offered by plant proteins, improved health consciousness among consumers has boosted the market for plant proteins. With the ever-increasing population, the need for alternative sources of protein is urgent. However, plant proteins possess inferior functional properties such as low solubility, emulsification and film-forming properties, which limit their use in food matrices. Cold plasma can be a sustainable and “green” method for modification of proteins, with minimal use of solvents and chemicals. The improvement in mechanical properties and biodegradability of the plant protein-based films by plasma treatment can be a great sustainable option for the industry. Apart from the mechanism of inactivation of enzymes, the immobilization of enzymes and fabrication of plant protein nanoparticles is also possible by cold plasma. Plasma improved the solubility, hydrophilicity, emulsifying and foaming properties of plant proteins. Prolonged exposure to cold plasma treatments had negative impact on the functional properties. However, plasma was successful in inactivating antinutritional factors and allergens in most proteins. Plasma treatments enhanced the adhesiveness of films, improving the composite formation of plant proteins with other films, with improved barrier properties.